Rejection on Gender Equality Draft Legislation: a Neglect against Indonesian Women’s Cultural History - Arivia, Gadis; Amzy, Nurulfatmi (Jurnal Perempuan, 2015)
The study examine Gender Equality and Justice bill (RUU KKG) debate in the parliament and why it failed or being postponed by the House of Representatives in 2014. Are religious views play a significant role in rejecting the bill? Or is KKG bill loaded with Western ideology and interests? Why are political parties reluctant to fight for women’s equality ? These are the questions explored in this study. The study also shows the lack of understanding of the history of Indonesian women’s movement and culture in the parliament.